A Review on Synthesis of Methane as a Pathway for Renewable Energy Storage With a Focus on Solid Oxide Electrolytic Cell-Based Processes - Biswas, Saheli; Kulkarni, Aniruddha P.; Giddey, Sarbjit; Bhattacharya, Sankar (Frontiers in Energy Research, 2020)
Environmental issues related to global warming are constantly pushing the fossil fuel-based energy sector towards an efficient and economically viable utilization of renewable energy. However, challenges related to renewable energy call for alternative routes of its conversion to fuels and chemicals by an emerging Power-to-X approach. Methane is one such high-valued fuel that can be produced through renewables powered electrolytic routes. Such routes employ alkaline electrolyzer, proton exchange membrane electrolyzer and solid oxide electrolyser, commonly known as solid oxide electrolytic cell (SOEC). SOEC has the potential to utilize the waste heat generated from exothermic methanation reaction to reduce the expensive electrical energy input required for electrolysis. A further advantage of SOEC lies in its capacity to co-electrolyze both steam and carbon dioxide as opposed to only water, and this inherent capability of SOEC can be harnessed for in-situ synthesis of methane within a single reactor. However, the concept of in-situ methanation in SOEC is still at a nascent stage and requires significant advancements in SOEC materials, particularly in developing cathode electrocatalyst that demonstrates activity towards both steam electrolysis and methanation reactions. Equally important is the appropriate reactor design along with optimization of cell operating conditions (temperature, pressure and applied potential). This review elucidates those developments along with research and development opportunities in this space. Also presented here is an efficiency comparison of different routes of synthetic methane production using SOEC in various modes, i.e., as a source of hydrogen, syngas, hydrogen/carbon-dioxide mixture and for in-situ methane synthesis.